VARIABILITY OF THE NUMBER AND WEIGHT OF 1000 SEEDS OF WEEDS PRESENT IN ALFALFA NATURAL SEEDS FROM DIFFERENT LOCATIONS IN SERBIA - Stanisavljević, Rade (Journal on Processing and Energy in Agriculture, 2023)
Alfalfa is the most significant perennial and multi-crop forage legume in Serbia. Seed production faces numerous problems, which causes high variability in seed yield. One of the problems in this production is the weed seeds that are in the natural alfalfa seed after harvesting. Minimum purity must be greater than 95 %, up to 2 % of other species are allowed, and up to 0.5 % of weeds, but no quarantine weeds such as dodder (Cuscuta spp.) and curly dock (Rumex spp.). Weed seeds were detected in natural alfalfa seeds: Sinapis arvensis L., Amaranthus retroflexus L., Rumex obtusifolius L., Cuscuta campestris Yunk., Rumex acetosella L., Plantago lanceolata L., Plantago major L., Rumex crispus L., Galium aparine L., Convolvus arvensis L. As expected, the variability of the number of weed seeds detected from the seed lots over three years was high: CV% = 14.78 for wild sorghum – S. halepense (L.) Pers. in the 2022, to CV% = 65.47 for ribwort plantain – P. lanceolata L in the 2020. For the mass of 1000 seeds of the examined weeds, the variability was determined from CV% = 5.869 for the ribwort plantain – P. lanceolata L. (year 2020), to CV% = 34.41 for yellow dock – R. crispus L. (year 2022).
Keywords: Key words: Number of weed seeds, natural alfalfa seeds, weight of 1000 weed seeds